TINJAUAN PERUBAHAN SISTEM PENGANGGARAN BERBASIS KINERJA DI INDONESIA - Suryanto Suryanto; Poni Sukaesih Kurniati (Jurnal Administrasi Publik dan Pembanguan, 2019)
This study aims to analyze changes in the performance-based budgeting system. The method used in this research is descriptive method with a qualitative approach. Data collection techniques using the study of literature. The results show that the budgeting system changes because, in the traditional budgeting system, there are many weaknesses in its implementation. The change of the budget system from the traditional budget system to a performance-based budgeting system was marked by the issuance of Law Number 17 of 2003 concerning State Finance. In reality, it turns out that the application of the performance-based budgeting system is still far from what was expected. There are several difficulties in implementing a performance-based budgeting system, namely the problem of agreeing on appropriate performance measures. Therefore, the implementation of a performance-based budgeting system is only limited to meet the provision.